PENINGKATAN PENGETAHUAN DAN SIKAP MASYARAKAT TENTANG IMUNISASI DASAR LENGKAP MELALUI EDUKASI KOMUNITAS TERPADU BERKELANJUTAN - Mizan Prihastuti; Siti Mahmudah; Berlina Putrianti; Siti Maryati; Saumi Fijriyah (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2026)
Complete basic immunization is an essential preventive measure to reduce morbidity and mortality among infants and toddlers. However, limited community knowledge and unfavorable attitudes remain challenges in achieving optimal immunization coverage. This community service activity aimed to improve community knowledge and attitudes toward complete basic immunization through integrated and sustainable community education. An educative–participatory approach with a pre-experimental one group pre-test and post-test design was applied. Educational activities were conducted through interactive counseling, group discussions, and question-and-answer sessions using educational media. Knowledge and attitudes were measured before and after the intervention using structured questionnaires and analyzed descriptively. The results showed an increase in community knowledge from moderate and low levels to predominantly good levels, along with a significant improvement in positive attitudes toward complete basic immunization. Community education proved effective in enhancing understanding and fostering supportive attitudes toward immunization programs. This activity is expected to serve as a sustainable promotive and preventive strategy to support the success of complete basic immunization programs.